α(M)β(2) is anti-atherogenic in female but not male mice - Szpak, Dorota (J Immunol, 2018)
Atherosclerosis is a complex inflammatory process characterized by monocyte recruitment into the arterial wall, their differentiation into macrophages and lipid accumulation. Since integrin α(M)β(2) (CD11b/CD18) mediates multiple diverse functions of leukocytes, we examined its role in atherogenesis. α(M)(−/−)/ApoE(−/−) and ApoE(−/−) mice were fed control or high fat diet (HFD) for 3 or 16 weeks to induce atherogenesis. Unexpectedly, α(M) deficiency accelerated development of atherosclerosis in female but not in male mice. The size of aortic root lesions was 3–4.5-fold larger in female α(M)(−/−)/ApoE(−/−) than in ApoE(−/−) mice. Monocyte/macrophage content within the lesions was increased 2.5-fold in female α(M)(−/−)/ApoE(−/−) mice due to enhanced proliferation. α(M)β(2) elimination promoted gender-dependent foam cell formation due to enhanced uptake of cholesterol by α(M)(−/−)/ApoE(−/−−) macrophages. This difference was attributed to enhanced expression of lipid uptake receptors, CD36 and scavenger receptor A1 (SR-A1), in female mice. Macrophages from female α(M)(−/−)/ApoE(−/−) mice showed dramatically reduced expression of FoxM1 transcription factor and estrogen receptors (ER) α and β. 17β-estradiol (E(2)) decreased CD36, SR-A1 levels and foam cell formation in ApoE(−/−) macrophages in ERα– and ERβ-dependent manner, as their antagonists inhibited the effect of E(2). However, female α(M)(−/−)/ApoE(−/−) macrophages failed to respond to E(2) and maintained elevated CD36, SR-A1 levels and lipid accumulation. FoxM1 inhibition in ApoE(−/−) macrophages reduced ERs and enhanced CD36, SR-A1 expression, while FoxM1 overexpression in α(M)(−/−)/ApoE(−/−) macrophages reversed their proatherogenic phenotype. We demonstrate a new, surprising atheroprotective role of α(M)β(2) in female ApoE(−/−) mice. α(M)β(2) maintains ER expression in macrophages and E(2)-dependent inhibition of foam cell formation.